Two Cases of Lupus vulgaris in Childhood and Review of the Clinical Challenges - Striegel, A. K.; Nazzal, R.; Fabri, M.; Rietschel, E.; Dötsch, J.; Mauch, C.; Tantcheva-Poor, I. (Klinische Pädiatrie, 2014)
Lupus vulgaris (LV) is the most common form of cutaneous tuberculosis (TB) in Europe, nevertheless the overall incidence is low. It constitutes about 1.5% of all extra-pulmonary cases worldwide. A slight raise in TB incidence rates among children was recently registered in Germany, which can be explained by the increased immigration.We present 2 cases of immigrated children who were diagnosed with Lupus vulagris, both clinically and histopathologically. Although the symptoms and the duration of the skin lesions were very different, both patients had a non-healing skin ulceration.In our cases cultures of the skin biopsy were positive for Mycobacterium tuberculosis and the lesions showed marked improvement in response to antituberculous treatment. In the first patient, it took 6 years between occurrence of skin lesions and final diagnosis. The second patient had an extracutaneous focus, namely abdominal TB.We report our experience and emphasize on recent advances in the diagnosis and treatment of paediatric skin TB.
Keywords: cutaneous tuberculosis; lupus vulgaris; scrophuloderm; tuberculosis cutis verrucosa